Workshop Penyusunan E-Modul Matematika Interaktif Penunjang Pembelajaran bagi Guru SMP - Susanto, Edi; Nur Aliyyah Irsal (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
The development of technology and information requires teachers to prepare online-based teaching materials for students. This is so that learning can not only be done in class but can be accessed at any time by students. This workshop activity aims to improve the ability of teachers in compiling interactive mathematics e-modules to support learning. The target of this workshop activity is a discussion group for mathematics subject teachers as many as 40 people who come from SMP/MTS Bengkulu City. Implementation of activities consists of: training, assignment, and evaluation. The results of the activity there is an increase in teacher knowledge in designing online teaching materials based on pretest and posttest data. The teacher's response after attending the workshop was good. Based on the activities carried out, it is very necessary for the school to hold training on the development of interactive teaching materials on an ongoing basis. Keywords: interactive e-module, teacher knowledge, workshop